The white tiger - Adiga, Aravind (HarperCollins, 2008)
Balram Halwai is a complicated man. Servant. Philosopher. Entrepreneur. Murderer. Over the course of seven nights, he tells the terrible and transfixing story of how he came to be a success in life with nothing but his own wits to help him along. Caught between his instinct to be a loyal son and servant and his desire to better himself, he learns of a new morality at the heart of a new India.